Labour shortage in Croatia: activities of trade companies - Bakotić, Danica; Veber, Natali (Oeconomica Jadertina, 2023)
The aim of this paper is to analyze the activities of trade companies that they could conduct in order to reduce the problem of labor shortage on Croatian labor market. Namely, this paper focuses on exploring the link between shortage of workers, unskilled and low skilled, as well as highly educated workers, and the various activities that companies can undertake to mitigate this problem. The empirical research was conducted through a specially designed questionnaire, on a sample of 30 large Croatian companies belonging to the trade industry. The results showed the modest activities of companies this field. Out of series activities that can diminish the problem of labor shortages, trade companies only undertake student scholarships and job sharing as an option only for women. The results of this paper will contribute to the understanding the situation on the labor market in Croatia. As we are aware, this is the first this kind of the research in Croatia, so it can be a starting point for a further research into this extremely important issue. However, due to the research limitations related to the small sample, the focus on only trade companies, the self-created survey questionnaire, that may have certain shortcomings and the applying of only correlation analysis; the obtained results must be considered in accordance with these limitations.
Keywords: shortage of workers; labor market; companies; activities